1977
DOI: 10.3109/10826087709027230
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Test and Demographic Variables Associated with Retention of Narcotic Addicts in Treatment

Abstract: The relationships of psychological and demographic variables to retention in treatment of narcotic addicts were examined. Age and race were not related to retention. The IQ's of subjects retained longer seemed to be higher but the relationship did not reach statistical significance with this sample size. Legal pressure was clearly associated with longer retention as were higher scores on the Suitable for Treatment Scale. Legal pressure seemed to exert its major influence early in treatment. Treatment center va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

1982
1982
2008
2008

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(4 citation statements)
references
References 3 publications
1
3
0
Order By: Relevance
“…The majority of those who had attempted suicide left. This finding adds to the picture provided by previous studies which have shown that depressed people tend to drop out of treatment (Brook & Whitehead, 1980;Kennard & Wilson, 1979;Linn et al, 1979;McFarlain et al, 1977). It could be that suicide attempt is an act of opting out and therefore predicts further opting out behaviour.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…The majority of those who had attempted suicide left. This finding adds to the picture provided by previous studies which have shown that depressed people tend to drop out of treatment (Brook & Whitehead, 1980;Kennard & Wilson, 1979;Linn et al, 1979;McFarlain et al, 1977). It could be that suicide attempt is an act of opting out and therefore predicts further opting out behaviour.…”
Section: Discussionsupporting
confidence: 79%
“…Among those which have been shown to have some importance are age, sex, race, marital status, educational background, employment history, criminal history, legal status, psychological symptomatology and previous treatment experience. There is evidence that those most likely to drop out are those with long or serious histories of drug abuse and antisocial behaviour, those who are depressed on admission, and, in some cases, those with severe psychopathology (Aron & Daily, 1976;Baekeland & Lundwall, 1975;Brook & Whitehead, 1980;De Leon & Rosenthal, 1979;Kennard & Wilson, 1979;Linn, Shane, Webb, & Pratt, 1979;McFarlain, Cohen, Yoder, & Guidry, 1977;Ogborne, 1978;Sansone, 1980). Sheffet et al (1975) found that different variables were related to retention in each of six programs in their study.…”
mentioning
confidence: 95%
“…However, a number of studies have reported no association between age and the likelihood of completing treatment (Claus, Kindleberger, & Dugan, 2002;Robinson & Little, 1982), making it difficult to draw definitive conclusions regarding age and treatment dropout. Race/ethnicity While some studies have reported that race has little effect on treatment dropout (McFarlain, Cohen, Yoder, & Guidry, 1977;Raynes & Patch, 1973;Sells, Chatham, & Joe, 1972), it has been suggested that Caucasians have higher completion rates than African Americans and Hispanics (Kleinman, Kang, Lipton, & Woody, 1992). In the majority of studies reporting differences in race/ethnicity, the role of race/ethnicity in dropout is not a primary aim, making it unclear from the results that these differences were not confounded by age, employment levels, or education levels.…”
Section: Demographic Variablesmentioning
confidence: 99%
“…A growing number of investigations have empirically explored potential predictors of substance use treatment dropout, including demographics (Maglione, Chao, & Anglin, 2000), psychiatric symptoms (Hattenschwiler, Ruesch, & Modestin, 2001), emotional symptoms (McCusker, Stoddard, Frost, & Zorn, 1996), drug use severity (Ravndal & Vaglum, 1991), and a variety of social-cognitive variables (e.g., social support, self-efficacy, motivation to quit; Blanchard, Morgenstern, Morgan, Labouvie, & Bux, 2003;Daley, Salloum, Zuckoff, & Kirisci, 1998;Mertens & Weisner, 2000;Messina, Wish, & Nemes, 2000). However, due to little agreement on the consistency or the generalizability of these findings (Claus, Kindleberger, & Dugan, 2002;McFarlain, Cohen, Yoder, & Guidry, 1977;Nemes, Wish, & Messina, 1999;Alterman, McKay, Mulvaney, & McLellan, 1996;Agosti, Nunes, Stewart, & Quitkin, 1991), it has become apparent that it is important to identify and examine other constructs that may contribute to the understanding of the processes involved in a patient's decision to remain in or prematurely leave residential treatment.…”
mentioning
confidence: 99%